Cervical cancer screening by cotesting method for Vietnamese women 25–55 years old: a cost-effectiveness analysis - Hien Thu Bui; Van Nu Hanh Pham; Thang Hong Vu (BMJ Open)
Background Cervical cancer (CC) is preventable through regular screening and vaccination against human papillomavirus (HPV). However, CC remains a significant public health issue in low-income and middle-income countries (LMICs) like Vietnam, where financial constraints hinder the widespread implementation of HPV vaccination and screening programmes. Currently, Vietnam lacks both a national CC screening intervention and an HPV vaccination programme for women and girls. To date, cost-effectiveness studies evaluating CC screening methods in Vietnam remain limited.Objectives To evaluate the cost-effectiveness of two CC screening strategies for Vietnamese women aged 25–55 years: (1) cotesting combining cytology and HPV testing conducted three times at 5 year intervals (intervention) and (2) cytology-based screening conducted five times at 2 year intervals (comparator). The objective is to provide evidence to inform policy and clinical practice in Vietnam.Design Cost-effectiveness analysis using a Markov model with 1 year cycles to simulate the natural progression of CC.Setting The Vietnamese healthcare system, modelled from the provider’s perspective, with parameters adapted to the local context through expert consultations.Participants A simulated cohort of Vietnamese women aged 25–55 years.Interventions The intervention involved cotesting (cytology and HPV testing) three times at 5 year intervals. The comparator was cytology-based screening conducted five times at 2 year intervals.Primary and secondary outcome measures The primary outcome measure was quality-adjusted life years (QALYs). Costs and cost-effectiveness ratios were assessed using Vietnam’s gross domestic product (GDP) per capita as the cost-effectiveness threshold (1–3 times GDP per capita). Sensitivity analyses (one-way deterministic and probabilistic) were conducted to account for uncertainties.Results The cotesting strategy was less effective and more costly than cytology-based screening across all age groups. Cotesting resulted in higher costs and fewer QALYs than the comparator. Probabilistic sensitivity analyses confirmed that cotesting was not cost-effective under current conditions in Vietnam.Conclusions Cytology-based screening conducted five times at 2 year intervals is a more cost-effective option for CC screening in Vietnamese women aged 25–55 years. The cotesting strategy cannot be recommended due to its higher cost and lower effectiveness.